Enhancing Maternal Engagement for Effective Stunting Prevention Strategies - Fadilla, Urshella Syintania; Choiriyah, Ilmi Usrotin (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Stunting is a critical public health issue that affects child development and overall community well-being. Effective management programs, such as the Pregnant Mother Class Program, are essential for addressing this challenge. Specific Background: In Wonoayu Village, Sidoarjo Regency, the implementation of this program aims to enhance maternal awareness and education regarding stunting prevention. However, the effectiveness of such programs in engaging the community remains underexplored. Knowledge Gap: While various studies have examined stunting management initiatives, limited research has focused on the qualitative aspects of community participation and communication in these programs. Aims: This research aims to evaluate the implementation of the Pregnant Mother Class Program in stunting management, specifically focusing on community participation, resource allocation, and bureaucratic structure. Results: Utilizing qualitative descriptive methods, the study found that while resource and disposition aspects were optimal, communication efforts were lacking, leading to low community awareness and participation. Training of facilitators was adequately conducted, but engagement with pregnant women required improvement. Novelty: This study provides unique insights into the dynamics of community education programs in stunting management, highlighting the critical role of communication in fostering community participation. Implications: The findings underscore the need for enhanced communication strategies to raise awareness and improve participation in health programs. Strengthening community engagement through targeted outreach can significantly enhance the effectiveness of stunting prevention initiatives, ultimately contributing to better health outcomes for mothers and children in rural settings. Highlights: Communication efforts require improvement for effective stunting management. Resource allocation and facilitator training were adequately implemented. Community participation enhances awareness and program effectiveness. Keywords: stunting prevention, pregnant mother class, community engagement, qualitative research, health education